PTSD, psychological morbidity and marital dissatisfaction in colonial war veterans - Pereira, M. Graça (2020)
Background: Forty years after Colonial War, veterans still show psychological disturbances affecting their marital and sexual satisfaction.Aims: This study analyzed the relationships between Post-Traumatic Stress Disorder (PTSD), number of PTSD symptoms and symptom clusters, psychological morbidity, marital dissatisfaction and sexual dissatisfaction; the variables that contributed to marital dissatisfaction and the mediator role of marital dissatisfaction and sexual dissatisfaction, in a sample of colonial War Veterans.Method: The sample included 138 Portuguese war veterans who answered Index of Marital Satisfaction; Index of Sexual Satisfaction; Beck Depression Inventory; State Trait Anxiety Inventory; Post-Traumatic Stress Disorder Scale.Results: PTSD, number of PTSD symptoms and symptom clusters were associated with psychological morbidity, marital and sexual dissatisfaction. Age, depression symptoms and sexual dissatisfaction contributed to marital dissatisfaction and the model explained 55% of the variance. Marital dissatisfaction mediated the relationship between depression symptoms and sexual dissatisfaction, as well as between number of PTSD symptoms and sexual dissatisfaction.Conclusions: Health professionals need to take into consideration the veteran's marital and sexual relationship in clinical routine consultations. As such, treating the veteran in the couple' context seems warranted.